Hubungan Lama Kerja Dengan Kejadian Nyeri Punggung Bawah Pada Penjahit Di Pusat Pasar Tradisional Kabanjahe - Lois Enika; Liza Agustin; Roni Roni (Jurnal Kesehatan dan Fisioterapi, 2023)
Background: : Low back pain is a very common world health problem, which causes activity restrictions and also absenteeism from work. Low back pain is a musculoskeletal complaint. Low back pain is a complaint that is not only experienced by elderly people but can also be found in all age categories, including productive adults. Sitting for a long time causes problems with lower back pain. This incidence is 60% in adults because of sitting problems that occur in those who work or excessive activities carried out in a sitting position. Because basically sitting for a long time and the wrong position can cause the back muscles to become tense and can damage the surrounding soft tissue. Objective: This study was conducted to determine the relationship between length of work and the incidence of low back pain in tailors at the Kabanjahe traditional market center. Method : Analytical descriptive research with Cross-Sectional approach. Placement of the sample using a total sampling technique with a total of 50 respondents. Measurement of low back pain using a questionnaire for moderate, mild and severe pain and measurement of length of work using a questionnaire on the length of work per day. Results: Based on the Shapiro-Wilk test, p value = 0.000 (p <0.05) which means that there is a relationship between low back pain in tailors. Conclusion: There is a relationship between length of work on low back pain in tailors at the market center.                                                                                          Keywords: Lower Back Pain, Length of Work, Tailor